PENGARUH ANALISIS JABATAN, PEMBERIAN BENEFIT DAN PERENCANAAN KARIR TERHADAP KINERJA PEGAWAI KPP PRATAMA BANTUL - Efendi, Nurman; Assery, Syeh (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
This study aims to: 1) analyze the effect of job analysis, provision of benefits and partial career planning on the performance of Pratama Bantul Tax Office employees, and 2) analyze the effect of job analysis, provision of benefits and career planning jointly (simultaneously) on employee performance Bantul Pratama Tax Office. The research method used was survey research and variables were measured using a Likert scale. The method of data collection was carried out using a questionnaire. The research was conducted using a purposive sample of 40 (forty) employees with Account Representative (AR) positions from a total population of 94 (ninety four) people and the analysis technique of this study used multiple linear regression with data processing using SPSS software.The results of the study stated that each variable, namely job analysis, benefit provision and career planning partially had a positive and significant effect on performance, so did the three job analysis variables, benefit provision and career planning together had a significant and significant effect on KPP Pratama Employee Performance Bantul. The coefficient of determination obtained in this study is 0.769, meaning that the performance variable is influenced by job analysis, benefit provision and career planning by 76.90%.